Green Product Marketing Strategy for Micro, Small, and Medium Enterprises in Digital-Based Markets - Tengku Kespandiar; Elizabeth; Rino Istarno; Nurlina; Ratnawita (Indonesian Journal of Business Analytics, 2026)
The biggest challenge has now shifted from why we should do it to how we finance and accelerate the transition. The implementation of a green economy has evolved from a mere theoretical concept to a major agenda for global and national policy. Its development is driven by the urgency of the climate crisis and the realization that conventional, exploitative economic growth is no longer sustainable. Green product marketing has undergone a major transformation, especially entering 2026. The focus is no longer simply on eco-friendly labels, but has become a strategic necessity and a key pillar in global and local business operations. This study aims to describe green product marketing strategy for micro, small, and medium enterprises in digital-based markets. The approach chosen to explain this presentation uses a qualitative approach based on strategic analysis. The Research results show that green product marketing by micro, small, and medium enterprises in digital-based markets is not just a trend, but rather a strategic response to shifting consumer behavior, which is increasingly concerned with environmental issues. These strategic responses include value-based narratives, green branding optimization, utilization of social proof, packaging strategies, community-based audience targeting, and price transparency.